COLLINEAR VOLUME HOLOGRAPHIC OPTICAL STORAGE SYSTEM AND INFORMATION STORAGE STRUCTURE THEREOF - SUN, Ching-Cherng; Yu, Yeh-Wei; Hsieh, Shu-Ching (My University, 2010)
A collinear volume holographic optical storage system records a plurality pages of holographic data on the storage material, where the intensity distribution of the saved recorded holographic data of each page is in a “+” format. It is possible to incur the inter-page cross talk between two adjacent pages of holographic data along the storage track or between two adjacent storage tracks. An rotation angle between the direction of the distribution of the volume grating and the direction of the storage track can be used to increase the descendent of data storage intensity along storage track, so the effect of the inter-page cross talk is decreased; or the distance between reading centers of two pages of holographic data is shorten to increase the storage density of the storage material.